Economic and agronomic optimum rates of NPS fertilizer for irrigated garlic (Allium sativum L) production in the highlands of Ethiopia - Yayeh, Shege Getu; Alemayehu, Melkamu; Haileslassie, Amare; Dessalegn, Yigsaw (Informa UK Limited, 2017)
Field experiment has been conducted in Yilmana Densa District during the 2014/2015 irrigation season with the objective of identifying the economical and agronomically optimum rate of the newly introduced NPS fertilizer for garlic production under irrigated smallholder farming system in the Highlands of Northwestern Ethiopia. Twelve NPS fertilizer rates, laid down on Randomized Complete Block Design with three replications were tested on local garlic variety. Accordingly, most of the growth and yield parameters were significantly affected by NPS fertilizer rates where non-fertilized plants were inferior in all parameters. Significantly highest plant height (69.23 cm) and above ground biomass (25.33 g) were recorded on garlic plants supplied with N:P2O5:S at the rate of 105:122.6:22.6 kg ha−1. Similarly, the biggest bulb diameter (4.27 cm) and the highest leaf number (13.4) as well as marketable (17.42 t ha−1) and total bulb yields (17.8 t ha−1) were recorded on plants which were supplied with 140:122.6:22.6 kg ha−1 N:P2O5:S that were similar with the effects of N:P2O5:S at the rate of 140:92:17 kg ha−1. N:P2O5:S at the rate of 140:92:17 kg ha−1 recorded the highest marginal rate of return that can be recommended to increase the yield of garlic and thus to improve the livelihoods of farmers in the study area.